Kalkulasi Biaya Produksi Dengan Bantuan Gemini - Nuryani, Anum; Fitriyana, Fina; Rosyati, Tati (Jurnal PKM Manajemen Bisnis, 2024)
MSME business actors often face a number of multidimensional problems, indicating that MSMEs have various complex problems. This indicates that MSME players are unable to calculate the Cost of Goods Sold accurately, so they experience problems in getting maximum profits. This is also experienced by MSME actors in the PAMULANG ESTATE WOMEN UMKM KUBE. Minimal expertise can be caused by many things, such as an educational background that is in line with the financial sector or MSME players who only focus on their production/business activities. This can be an obstacle for MSMEs in calculating the basic price and determining the selling price. Generally, MSME players only follow market prices without knowing how much profit they actually get. The increasing technological developments should further help MSMEs in improving their performance. The results of observations and surveys carried out by the service team provide an illustration that the MSME actors in KUBE WANITA UMKM PAMULANG ESTATE are still unfamiliar with calculating COGS or Production Cost Calculations. As a form of our embodiment in carrying out the tri dharma of higher education. We collaborate with KUBE WOMEN UMKM PAMULANG ESTATE to carry out community service. The activity will be held on April 27-28 2024 by discussing cost calculations using AI to make things easier for MSMEs. Through this service activity, it is hoped that MSME players will no longer experience difficulties in classifying costs and calculating production costs where these costs determine the selling price.